Electrochemical Behaviour of Actinides and Fission Products in Room-Temperature Ionic Liquids - K. A. Venkatesan; Ch. Jagadeeswara Rao; K. Nagarajan; P. R. Vasudeva Rao (International Journal of Electrochemistry)
In the recent past, room-temperature ionic liquids (RTILs) are being explored for possible applications in nuclear fuel cycle. RTILs are being studied as an alternative to the diluent, n-dodecane (n-DD), in aqueous reprocessing and as possible substitute to high-temperature molten salts in nonaqueous reprocessing applications. This paper deals with the current status of the electrochemical research aimed at the recovery of actinides and fission products using room-temperature ionic liquid as medium. The dissolution of actinide and lanthanide oxides in ionic liquid media and the electrochemical behavior of the resultant solutions are discussed in this paper.